PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI (Studi Empiris di Kabupaten / Kota se-Jawa Tengah) - Catur Santoso, 08.05.52.0128; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2014)
This study aims to provide empirical evidence about the effect of local revenue and Capital Expenditure on economic growth in the District / City of Central Java.The population in this study is 35 (thirty five) District / City of Central Java with a sample size equal to the population from 2010 to 2012.analysis technique using by multiple linear analysis regression.These results prove that the original income positive and significant effect on Economic Growth, as well as capital expenditures and significant positive effect on economic growth in the District / City of Central Java. Thus, the local government / municipalities in Central Java this study are expected to be useful in formulating policies and strategies that are effective, efficient, and economical stimulus for activity against the Regional Economic Growth in Central Java. Keywords: Regional Income, Capital Expenditure and Economic Growth